A PROGRAM FOR GRADUATE STUDY OF ACCOUNTING. - Taylor, Jacob B. (The Accounting Review, 1932)
Abstract In late years the number of students who have enrolled for the courses in the accounting curriculum in collegiate schools of business has been increasing tremendously. This increase is almost appalling when one considers the strain which is being placed upon the educational set-up, particularly as it applies to the accounting courses. A program of work which has been outlined for small groups of students becomes totally inadequate when the numbers increase to considerable proportions. Coupled with the adjustments which may be necessary because of larger classes, there is also the responsibility of recognizing present-day trends in accounting and business and adapting the accounting curriculum to these trends. The problem of critical analysis of the curriculum is one which is often delayed indefinitely, if not put off altogether. That there is need for such analysis and probably for much change cannot be denied. Most curricula in accounting are the result of haphazard growth and not of careful planning. There is very definitely a challenge in the present situation for colleges to appraise carefully the equipment needed by the accounting-trained man in the years ahead of him and to adapt the training given him to that need.